2002
DOI: 10.1002/j.2050-0416.2002.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Complexity of the Nitrogen Source and Influence on Yeast Growth and Fermentation

Abstract: The structural complexity of the nitrogen source strongly affects both biomass and ethanol production by industrial strains of Saccharomyces cerevisiae, during fermentation in media containing glucose or maltose, and supplemented with a nitrogen source varying from a single ammonium salt (ammonium sulfate) to free amino acids (casamino acids) and peptides (peptone). Diauxie was observed at low glucose and maltose concentrations independent of nitrogen supplementation. At high sugar concentrations diauxie was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 47 publications
(53 reference statements)
5
60
2
4
Order By: Relevance
“…Ammonium sulfate always induced lower fermentative performance in all conditions used in this study. These results differ from the previously reported study in media containing glucose and maltose, which showed that peptone, a nitrogen source where amino acids predominate in the peptide form, was more efficient for yeast growth and fermentation 7 . Lower biomass accumulation in the media supplemented with ammonium sulfate was detected in both studies and this resulted from the yeast using the carbohydrate as a carbon and an energy source.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Ammonium sulfate always induced lower fermentative performance in all conditions used in this study. These results differ from the previously reported study in media containing glucose and maltose, which showed that peptone, a nitrogen source where amino acids predominate in the peptide form, was more efficient for yeast growth and fermentation 7 . Lower biomass accumulation in the media supplemented with ammonium sulfate was detected in both studies and this resulted from the yeast using the carbohydrate as a carbon and an energy source.…”
Section: Discussioncontrasting
confidence: 99%
“…Improved ethanol production by the baking yeast strain Fiso was observed in the medium supplemented with casamino acids when compared with peptone and ammonium sulfate, with higher biomass accumulation and faster fermentation. The results with galactose media differ from those with glucose and maltose media, where high sugar concentrations were found to induce higher biomass and ethanol production in the media supplemented with peptone 7 .…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations